TEACHER-CENTERED VS STUDENT-CENTERED METHODS IN ENGLISH LANGUAGE TEACHING - Mukhtasarkhon Dadajonova (International Journal of Literature and Language Studies, 2026)
The choice of teaching methodology significantly influences the effectiveness of English language instruction. Among the most widely discussed approaches are teacher-centered and student-centered methods. This study aims to compare these two instructional approaches and examine their impact on learners’ engagement, language development, and classroom interaction.